Medical devices : surgical and image-guided technologies - Culjat, Martin , 1977-; Lee, Hua , 1952-; Singh, Rahul (John Wiley & Sons, 2013)
"Biomedical Devices and Technology is a textbook for an introductory seminar course on biomedical devices and technology. The book covers devices and systems in diagnostic, surgical, and implant procedures, prepared by the much-respected faculty members at the UCLA School of Medicine" -- Provided by publisher.